2022
DOI: 10.1111/liv.15286
|View full text |Cite
|
Sign up to set email alerts
|

Impact on follow‐up strategies in patients with primary sclerosing cholangitis

Abstract: Background & Aims: Evidence for the benefit of scheduled imaging for early detection of hepatobiliary malignancies in primary sclerosing cholangitis (PSC) is limited.We aimed to compare different follow-up strategies in PSC with the hypothesis that regular imaging improves survival. Methods:We collected retrospective data from 2975 PSC patients from 27 centres. Patients were followed from the start of scheduled imaging or in case of clinical follow-up from 1 January 2000, until death or last clinical follow-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 27 publications
0
14
0
1
Order By: Relevance
“…However, there is a paucity of studies demonstrating the effectiveness of biomarker-and imaging-based surveillance in reducing CCA mortality. However, three retrospective studies provide evidence for the potential survival benefit of CCA imaging surveillance in PSC [44][45][46]. A study of 830 PSC patients from Mayo Clinic Rochester found patients with imaging surveillance had significantly increased overall survival in patients with CCA (hazard ratio 0.22, 95% confidence interval 0.12-0.41; p<0.001) [45].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is a paucity of studies demonstrating the effectiveness of biomarker-and imaging-based surveillance in reducing CCA mortality. However, three retrospective studies provide evidence for the potential survival benefit of CCA imaging surveillance in PSC [44][45][46]. A study of 830 PSC patients from Mayo Clinic Rochester found patients with imaging surveillance had significantly increased overall survival in patients with CCA (hazard ratio 0.22, 95% confidence interval 0.12-0.41; p<0.001) [45].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Similarly, yearly imaging was associated with twofold reduction in hepatopancreatobiliary cancers in patients with PSC with concurrent inflammatory bowel disease [46]. Bergquist et al assessed the effects of imaging surveillance strategies from twenty-seven centres from twelve western countries [44]. The authors found scheduled imaging surveillance was associated with a lower risk of overall mortality (hazard ratio 0.61 (0.47-0.80) and improved survival after CCA diagnosis compared to patients without scheduled imaging.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation
“…Erste Studien zeigen, dass regelmäßige Vorsorgeuntersuchungen dazu beitragen können, hepatobiliäre Malignome in früheren Stadien zu entdecken 42 , 43 . Dies wurde jedoch in einer kürzlich vorgestellten, prospektiven Studie aus Schweden – bei allerdings sehr geringer Inzidenz hepatobiliärer Tumoren – nicht bestätigt 44 , 45 .…”
Section: Primär Sklerosierende Cholangitis (Psc)unclassified
“…Management and follow‐up strategies for PSC vary considerably between centres and countries, 9,10 likely due to the lack of evidence‐based practice in PSC. Furthermore, they vary according to the age of the patients due to differences in disease course.…”
Section: Introductionmentioning
confidence: 99%